2007
DOI: 10.1007/s00431-007-0550-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis by rotavirus in Spanish children. Analysis of the disease burden

Abstract: Rotavirus is one of the most common causes of gastroenteritis worldwide. With the commercialisation of effective rotavirus vaccines in Europe in sight, it is necessary to provide studies which evaluate the disease burden. The aim of this study is two-fold, on one hand, to determine the burden of the rotavirus disease in Spanish children under the age of five, and on the other, to estimate the economic cost of these hospitalizations. The study was undertaken during a 5 year period (2000-2004). The rotavirus hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
2
7
0
9
Order By: Relevance
“…Furthermore, as described by other authors [6,8,18,24,26,32], the highest incidence was found in children between 6 and 24 months of age (38%), with a prevalence in males (55.6%). However, there was an unexplained high rate of all patients hospitalized for RVGE who were 5 years of age or older.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, as described by other authors [6,8,18,24,26,32], the highest incidence was found in children between 6 and 24 months of age (38%), with a prevalence in males (55.6%). However, there was an unexplained high rate of all patients hospitalized for RVGE who were 5 years of age or older.…”
Section: Discussionsupporting
confidence: 60%
“…This incidence looked much higher compared with an incidence of 3.8 and 4.9 per 1,000 child-years observed in two other sentinel hospitals in another region of Japan [Kamiya et al, 2009]. The incidence of rotavirus hospitalizations in Japan (a median of 9.0 in the four reports from Japan) was similar to the median incidence of 7.8 per 1,000 children less than 5 years of age (range: 2.5-20.0) in 11 developed countries [Nakagomi et al, 2005[Nakagomi et al, , 2009Nelson et al, 2005;Podewils et al, 2005;Lu et al, 2006;Chen et al, 2007;Fischer et al, 2007;Huet et al, 2007;Jit and Edmunds, 2007;Newall et al, 2007;Widdowson et al, 2007;Goossens et al, 2008;Luquero et al, 2008;Melliez et al, 2008;Kamiya et al, 2009;Martin et al, 2009;Panatto et al, 2009;Wu et al, 2009].…”
Section: Discussionsupporting
confidence: 55%
“…Data about RV morbidity in Europe are available mainly for southern [2,9,26], northern [16,31], and western parts [1,3,6,11,28]. Only a few studies were performed in eastern Europe [22].…”
Section: Introductionmentioning
confidence: 99%